Map of homicides by firearms: profile of the victims and the assaults - Ruth França Cizino da Trindade; Flávia Azevedo de Mattos Moura Costa; Patrícia de Paula Alves Costa da Silva; Gustavo Bussi Caminiti; Claudia Benedita dos Santos (SciELO, 2015)
AbstractOBJECTIVEDescribing the profile of victims and assaults by gunshot, where the outcome was death.METHODAn ecological study conducted in the city of Maceió/AL, in 2012. Data were collected from the death statements. The variables studied were: the death circumstances, gender, age, marital status, place, date, time, month and proportion according to the occurring neighborhood.RESULTSThe homicide mortality rate was 65.2 per 100,000 inhabitants, with 130.6 per 100,000 men and 7.8 per 100,000 women. Of the total number of homicides, 93.6% of the victims were men. The age group between 15 and 29 years of age was the most affected, with 68.8%. In 97.6% of cases the death occurred at the site of aggression, 74.1% in the streets. In relation to the date, 54.2% of cases occurred between Friday and Sunday. 59.7% of the homicides were concentrated in seven neighborhoods.CONCLUSIONThe map of violence presented shows heterogeneous areas for the occurrence of assaults with firearms, characterizing the existing urban inequality in violence distribution.